APPLICATION OF MOLECULAR MARKERS IN BREEDING FOR RESISTANCE TO POTATO CYST NEMATODE - V. A. Biryukova; I. V. Smiglya; S. B. Abrosimova; V. V. Manankov; A. V. Mityushkin; E. V. Rogozina; S. D. Kiru; N. A. Chalaya; A. A. Meleshin; V. A. Zharova (Труды по прикладной ботанике, генетике и селекции)
The article presents the results of the application of molecular markers of the genes controlling resistance to potato cyst nematode in different stages of potato breeding - for screening genetic collections and promising hybrids of the All-Russian Institute of Potato Research and the Vavilov Institute of Plant Genetic Resources. It has been established that "pseudopositive" and "pseudonegative" results of a marker-mediated breeding process are associated not only with the specificity of the used markers, but with a lack of objectivity in phenotypic evaluation for resistance to the nematode.